(untitled) (Materiali di Estetica. Terza serie, 2023)
The concept of "color" is invoked in music from the simplest pieces and is initially related to the range of intensity. Then it perfects itself in the ability to create a more complex relationship between elements such as timbre, style of writing, breath and articulation of language, acoustics of space. The palette becomes rich and complex. Among the instruments, the harpsichord is an extraordinary testing ground for musical colours, particularly in the French repertoire.